Bentuk Penerapan Reward dan Punishment yang Diberikan Orangtua untuk Memotivasi Belajar Anak Usia Remaja Awal di Kabupaten Agam - Syahrias, Ryan (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
The purpose of this study was to determine the form of application of rewards given by parents tomotivate adolescent children's learning, and the form of application of punishment given by parents to motivate adolescent learning in Agam district. Focus on the problem raised, how is the form of reward and punishment given by parents to increase learning motivation for early adolescent children in Agam Regency. In collecting data, researchers used qualitative research methods, namely conducting observations and interviews. The results of this study are from the results of research that the author did about the form of application of reward and punishment applied by parents to their children showing a positive impact in supporting success in increasing their children's learning motivation at home and at school. This can be seen from the results of the research that the author did, that when children are given rewards, their learning motivation increases, increases and children try to improve their achievements in school. Meanwhile, when achild is given punishment, the child's motivation also increases and increases and also tries toimprove his performance, who was lazy to study or delay learning after being given punishment, the child becomes willing to learn and does not delay anymore. The form of reward applied by parents is in the form of giving praise, awards, and prizes. While the forms of punishment applied by parents are in the form of reprimands, warnings, and punishments.